Long period grating in a multimode cyclic transparent optical polymer fiber inscribed using a femtosecond laser - Theodosiou, Antreas; Min, Rui; Leal-Junior, Arnaldo; Ioannou, Andreas; Frizera, Anselmo; Pontes, Maria José; Marques, Carlos Alberto F.; Kalli, Kyriacos (My University, 2019)
In this Letter, we report, to the best of our knowledge, the first inscription of long period gratings (LPGs) in a multimode cyclic transparent optical polymer (CYTOP) fiber using a femtosecond laser inscription method. The LPG was inscribed directly in the center of the fiber core, tailored for operation at 1560 nm. The CYTOP-LPG was characterized in transmission, and its response for relative humidity and temperature was measured. The humidity measurements, to the best our knowledge, are the first for a POF-LPG, whereas the temperature sensitivity is significantly higher than reported in other works. In addition, dynamic mechanical measurements were performed comparing the mechanical characteristics of the laser exposed sections of the polymer fiber, where the LPG was inscribed, with the unexposed regions.
Keywords: Femtosecond lasers; Fiber optic sensors; Polymers; Relative humidity and temperatures; Femtosecond laser inscriptions; Temperature sensitivity; Unexposed regions